Fourier Transform Infrared Spectroscopic FTIR Study on Arsenic Induced in Gill Tissue of Freshwater Fish Ctenopharyngodon idella - Ananth, S (International Journal of Pharmaceutical & Biological Archive, 2015)
Fourier Transform Infrared Spectroscopic FTIR Study on Arsenic Induced in Gill Tissue of Freshwater Fish Ctenopharyngodon idella